2012
DOI: 10.1017/brimp.2012.7
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Methods Study of the Experience of Transition to the Community of Working-Aged People with Non-Traumatic Brain Injury

Abstract: Background and aims: The 'transition' phase from hospital to home following brain injury is well established as a critical period of adjustment for individuals and their families. There is, however, a lack of knowledge about the experience of transition following nontraumatic brain injury (e.g., stroke, aneurysm) for individuals of working age. The purpose of this study was to explore the transition experiences of individuals with nontraumatic brain injury using mixed methods approach. Methods: Six individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…For example, research suggests that, given the effects of TBI, some workers lose confidence in their ability to satisfy job demands [3,5]. This lack of confidence may explain why one of the participants was concerned that others might think he was not doing a good job.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, research suggests that, given the effects of TBI, some workers lose confidence in their ability to satisfy job demands [3,5]. This lack of confidence may explain why one of the participants was concerned that others might think he was not doing a good job.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for a lack of fit between a person and a job is obvious in any review of TBI symptoms, which include cognitive difficulties (e.g., memory, reading, listening, organizing, and reasoning difficulties), emotional issues (e.g., problems with depression, anger management, and anxiety), physical effects (e.g., headaches, speech problems, lack of coordination, and fatigue), and psychosocial problems (e.g., feeling misunderstood, being bullied or teased, and being perceived by others as malingering or not performing consistent with capabilities [2,5,7]. Most people with TBI are employed at the time of their injuries, but only 31 percent are employed one year later [8].…”
Section: Tbi's Impact On Personal Functioning and Job Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been identified that this population experiences difficulties that only become apparent when they begin to reintegrate into daily living and the associated complex activities (Tellier & Rochette, 2009). This time from acute hospital discharge back to home and community life can be identified as the transition period and for people with mild stroke it is one of the most influential times in the recovery continuum (Hall, Grohn, Nalder, Worrall, & Fleming, 2012). This is because it is a time in which their perceptions of themselves are challenged as difficulties emerge, resulting in a need to develop new routines and accept ongoing changes (Glass & Maddox, 1992;Goodman, Scholssberg, & Andersson, 2006;Hall et al, 2012).…”
Section: Rationale For Thesismentioning
confidence: 99%
“…This time from acute hospital discharge back to home and community life can be identified as the transition period and for people with mild stroke it is one of the most influential times in the recovery continuum (Hall, Grohn, Nalder, Worrall, & Fleming, 2012). This is because it is a time in which their perceptions of themselves are challenged as difficulties emerge, resulting in a need to develop new routines and accept ongoing changes (Glass & Maddox, 1992;Goodman, Scholssberg, & Andersson, 2006;Hall et al, 2012). Difficulties experienced by this population span all domains of human functioning including: cognition, physical functioning and emotional well-being, consequently impacting the completion of daily activities (Taule & Råheim, 2014).…”
Section: Rationale For Thesismentioning
confidence: 99%